Rheumatoid Arthritis Patients have Similar Excellent Outcomes after Total Knee Replacement Compared with Osteoarthritis Patients - Goodman, Susan M. (J Rheumatol, 2015)
OBJECTIVE: Although new treatments for rheumatoid arthritis (RA) are extremely effective in preventing disease progression, rates of total knee replacement (TKR) continue to rise. The ongoing need for TKR is problematic, especially as functional outcomes have been reported to be worse than in patients with osteoarthritis (OA). The purpose of this study is to assess pain, function, and quality of life 2 years after TKR in a contemporary RA patients, compared to patients with OA. METHODS: Primary TKR cases enrolled between 5/1/2007 and 7/1/2010 in a single institution TKR registry were eligible for this study. Validated RA cases were compared to OA at baseline and at 2-years. RESULTS: We identified 4,456 eligible TKRs, including 136 RA. Compared to OA, RA TKR had significantly worse pre-operative WOMAC pain (55.9 vs. 46.6; p-value<0.0001) and function (58.7 vs. 47.3; p-value<0.0001) , however there were no differences at 2 years. Within RA, there was no difference for patients who used biologic DMARDs vs. those who did not in pain (p-value= 0.41) or function (p-value= 0.39) at 2 years. In a multivariate regression, controlling for multiple potential confounders, there was no independent association of RA with 2-year pain (p-value=0.18) or function (p-value=0.71).Satisfaction was high for both RA and OA. CONCLUSION: RA patients undergoing primary TKR have excellent 2-year outcomes, comparable to OA, in spite of worse pre-operative pain and function. In this contemporary cohort, RA is not an independent risk factor for poor outcomes.